Designing for Interaction - Sackville, Andrew D. (Proceedings of the International Conference on Networked Learning, 2002)
A common challenge facing those educators involved in online learning revolves around finding ways of sustaining student activity in asynchronous learning environments. This paper seeks to reflect on the design and evaluation of a number of online programmes which have been run at Edge Hill over the last three years. It will relate the intentions of the programme designers, informed by a common model of pedagogy, to the actual patterns of interaction which took place on the programmes. Using evaluation and action research to inform and amend design has been a feature of the programmes; and the paper concludes that design and redesign are essential but often overlooked components in developing and delivering online learning opportunities.